Exploring The Current State Of Lean Practices In The Agri-Food Supply Chain: A Systematic Literature Review - Puti Fitri Larasati; Nur Budi Mulyono (Politeknik Negeri Bandung, 2022)
The increasing importance of the agriculture and food industry, due to the growing population and competitive business landscape, has driven the need to increase the efficiency and effectiveness of organisational and supply chain processes. Lean practices have been proposed to help reduce wastage, improve processes, and give more value to customers. However, research and debates on the implementation of lean practices in the agri-food industry are still limited. Therefore, this study aims to explore the current knowledge state of lean practices under the agri-food supply chain process by using a systematic literature approach. Additions for future research areas are also identified and presented. Our review suggests that the study of the lean concept in the context of agri-food supply chain is still limited and thus is open for future exploration. Furthermore, future research employing multiple methods, focusing on the downstream actors in the supply chain and empirical evaluations of lean impacts is encouraged. The contribution of this study will provide an insight for scholars of current and future research opportunities to explore. At the same time, practitioners can gain knowledge of lean practices and tools that might be applied to their business contexts.